Complete androgen insensitivity syndrome: Case based review article - Babulreddy (Journal of Medical and Scientific Research, 2015)
Complete androgen insensitivity syndrome (CAIS) a form of 46 XY disorder of sex development (DSD), usually presents with an inguinal hernia in an infant or a child and with primary amenorrhea in adult phenotypic female. We hereby report a case who reared as a female presented to us with primary amenorrhea and on further evaluation, diagnosed to have CAIS, then we also discuss in detail about this rare entity.